Mapping The Strategy Of Development Of The Creative Economy South Tangerang-Based Prospective Analysis - Nur Aini (CV. AFDIFAL MAJU BERKAH, 2022)
The creative economy is one of the boosters in spurring economic development in South Tangerang City. Activities that support economic growth where production, distribution and consumption become a unified chain that is interconnected between creative economic actors, distribution chains, consumers and the government as regulator. The purpose of this study is to map the strategic development of a creative economy based on prospective analysis in South Tangerang. The primary data collection method was done by interview and direct observation to the field. Secondary data collection was taken from literature review. Analysis of data used prospective analysis. The results showed that the average star up did not have legality, consequently access to capital was difficult. Capital and product development are variables that have a very strong dependency and influence in the development of the creative economy, and which are included in this output variable are processing facilities, availability of raw materials, employment, revenue, packaging, shelf life, business meeting. Suggestions that can be given related to the results of this research are the socialization of legality management needs to be improved and the need for training according to the creative economy business category in South Tangerang.